2014
DOI: 10.1073/pnas.1419038112
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of a human-associated TM7 phylotype reveals a reduced genome and epibiotic parasitic lifestyle

Abstract: The candidate phylum TM7 is globally distributed and often associated with human inflammatory mucosal diseases. Despite its prevalence, the TM7 phylum remains recalcitrant to cultivation, making it one of the most enigmatic phyla known. In this study, we cultivated a TM7 phylotype (TM7x) from the human oral cavity. This extremely small coccus (200-300 nm) has a distinctive lifestyle not previously observed in human-associated microbes. It is an obligate epibiont of an Actinomyces odontolyticus strain (XH001) y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
547
3
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(610 citation statements)
references
References 43 publications
27
547
3
2
Order By: Relevance
“…Based on information available from hundreds of genomes from genome-resolved metagenomics and single-cell genomics methods to date, all members have relatively small genomes and most have somewhat (if not highly) restricted metabolic capacities 7,13,24 . Many are inferred (and some have been shown) to be symbionts 7,25,26 . Thus far, all cells lack complete citric acid cycles and respiratory chains and most have limited or no ability to synthesize nucleotides and amino acids.…”
Section: Korarchmentioning
confidence: 99%
“…Based on information available from hundreds of genomes from genome-resolved metagenomics and single-cell genomics methods to date, all members have relatively small genomes and most have somewhat (if not highly) restricted metabolic capacities 7,13,24 . Many are inferred (and some have been shown) to be symbionts 7,25,26 . Thus far, all cells lack complete citric acid cycles and respiratory chains and most have limited or no ability to synthesize nucleotides and amino acids.…”
Section: Korarchmentioning
confidence: 99%
“…The recently cultivated TM7 strain TM7x has a reduced genome of 705 kb, which lacks the genes necessary for essential amino acid biosynthesis; consequently, it is incapable of independent growth and leads an obligately symbiotic relationship with another bacterium, Actinomyces odontolyticus (He et al 2015). Davis et al (2013) also showed that gene loss in bacteria is associated with auxotrophy for purine, pyrimidine, fatty acid, and amino acid synthetic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The recent successful isolation of a member of the phylum TM7 by He et al (24) has shown that the relationship between oral bacteria can be more intimate, with the demonstration that the TM7 organism isolated has an intracellular lifestyle, growing within the cells of another species.…”
Section: Discussionmentioning
confidence: 99%